Recurrent and recalcitrant upper lid cicatricial entropion following combined chemotherapy: Clinical and pathology correlation - Galindo-Ferreiro, Alicia (2021)
We report a case of recalcitrant bilateral upper eyelid cicatricial entropion associated with distichiasis/trichiasis which followed an adjuvant systemic chemotherapy. The chemotherapy, administered for treatment of breast cancer, consisted of docetaxel, carboplatin, and herceptin. Shortly following the combined chemotherapy treatment, epiphora and eyelash abnormalities commenced. The patient presented with a swollen eyelid margin and tarsal conjunctival inflammation associated with cicatricial entropion and diffused distichiasis/trichiasis affecting the upper lids, with greater severity observed in the medial portion. Despite manual epilation and multiple argon laser sessions, no improvement was noted. Surgical treatment was performed using a lid split, distichiasis excision of the right upper lid, and homolateral tarsoconjunctival graft. The biopsy examination showed chronic inflammation, dermal fibrosis with squamous metaplasia process, and an abnormal epithelial differentiation. After 6 months, entropion recurred. Tarsal marginal rotation associated with posterior lamella advancement was performed. However, cicatricial entropion and distichiasis/trichiasis recurred. The patient was prescribed bandage contact lenses and topical lubrication to relieve symptoms.